Trump’s Aesthetic, Spatial and Architectural Dramalities - Sophie Suma (Footprint)
This article hypothesises that while drama is primarily a television genre, its operation also appears in the way Trump mediates his political activities. By observing some of the media objects and events staged by Trump, such as his escalator descents from Trump Tower, the popularisation of Trump’s Border Wall, the attempt to institutionalise the executive order entitled ‘Making Federal Buildings Beautiful Again’, and the transgression of national symbolic spaces embodied by the 4 July 2019 show at the Lincoln Memorial in Washington, DC, it will be a matter of questioning the architectural politics conducted by Trump. Then to see in what way the Trumpian dramatisation participates in a populist architectural strategy.